Mode I fracture characterization of wood using the TDCB test - de Moura, M.F.S.F. (2018)
The Tapered Double Cantilever Beam test (TDCB) was analysed in the context of wood fracture characterization under mode I loading. A simpler linear slender increase of the cross-section is proposed to replace with accuracy the contoured nonlinear specimen proﬁle, dictated by the presence of non-negligible shear eﬀects. A ﬁnite element analysis including cohesive zone modelling was performed considering three diﬀerent data reduction schemes: compliance calibration, Mostovoy and compliance based beam method (CBBM). All the methods provided good agreement in the plateau region of the Resistance-curves with the value of fracture energy used as input in the numerical simulation, especially the Mostovoy and CBBM ones, which have the remarkable ad-vantage of being independent of crack length monitoring during the test. Additional experimental and numerical analyses were performed to settle the validity of the proposed approaches. All the results conﬁrm the appropriateness of the TDCB test with linear tapering and proposed data reduction schemes as valuable tools for suitable wood fracture characterization under mode I loading.